RANCANG BANGUN SISTEM INFORMASI PENJUALAN ONLINE PADA TOKO PONDOK BUSANA - Nasril Nasril; Dwiva Shabrina Yuselfira (POLITEKNIK LP3I JAKARTA, 2025)
The problem encountered at Pondok Busana Store is the difficulty in conducting sales transactions with remote customers due to the prevalence of Covid-19 cases. Therefore, an accurate, efficient, and fast system is needed to market products and serve customers remotely. Sales at Pondok Busana are still manual and ineffective, which causes many problems in sales, such as in marketing products and the large number of books used to record all orders, which takes a long time and can lead to errors in data management. The author wants to create an online program system that does not require customers to come to the store and makes it easier for the store to conduct sales transactions. The solution provided by the author is expected to simplify the process by creating a computerized system that can be applied to the Pondok Busana store, thereby providing faster, more precise, and accurate services in transactions so that the business runs smoothly and efficiently.